The e-CF - a sector framework for professional competences in IT : Findings from the application of the e-CF in the modernisation of IT occupations - Kennecke, Angela [Verfasser]; Felkl, Thomas [Verfasser] (My University, 2020)
"Sector frameworks are gaining in significance as part of the endeavour to make national qualification profiles more transparent in European comparative terms and to render them more readily understandable. The European e-Competence Framework (e-CF) represents just such an instrument for the IT sector. When the IT occupations were revised, it was used as a supplementary reference in order to map the skills, knowledge and competences contained in the new general training plans. This article provides an initial introduction to the development and structure of the e-CF. It also states the findings and outcomes that have emerged from the revision process and illustrates areas of potential for application and further development." (authors' abstract; BIBB-Doku)
Keywords: S 6.4.9 IT-Berufe; I 2.2 Europa; IT-Beruf; Neuordnung der Ausbildungsberufe; Modernisierung; E-Competence Framework; Kompetenzprofil